Investigating the Contribution of Blogging Interactions to Preservice English Language Teachers’ Reflection and Construction of Teacher Identity - Sallı, Ayşegül (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The purpose of the study was to investigate the contribution of blogging to preservice teachers’ reflection and construction of teacher identity. A blog tool was integrated in the Teaching Practice course in order to address the need for more interaction caused by limited in-class hours. An action research study was carried out in two cycles, in the fall semesters of 2011-2012 and 2012-2013, with a total of 15 preservice teachers studying at the Foreign Language Education Department of Eastern Mediterranean University. Data comprised semi-structured interview reports and preservice teachers’ blog posts (i.e., teaching practice lessons reflection blog entries, movie critiques, final reports and comments). Frequency analysis was conducted to find out about the preservice teachers’ blog participation. The results show that all the preservice teachers in the first cycle took part in the blogging by posting the required blog tasks. However, since participation was on voluntary basis in the second cycle, not all participants posted their blog tasks. Preservice teachers’ interactions with one other on the blog were found to be at different levels. A number of hindering reasons such as lack of participants’ familiarity with and attitudes towards the blog tool, perceived adequacy of written expression, and group dynamics were discovered. An adapted framework was used to reveal the levels of reflections in preservice teachers’ teaching practice lessons reflection blog entries. The results indicated that most of the participants’ reflections were at descriptive level which included their feelings and teaching practice experiences. It should be noted that only a few participants linked these to theories and elaborated on their future plans for improvement. Possible-selves theory guided the analysis of data to understand the contribution of preservice teachers’ blogging interactions to construction of their teacher identity. According to the results, sharing reflections on teaching practice experiences and reflecting on various teacher characteristics influenced how they shaped their concepts about qualities of good teachers. This in turn led to the emergence of expected and feared possible selves. Preservice teachers mostly articulated what kind of teacher they expect to be and avoid becoming, in the areas of interpersonal relationships, instructional strategies and classroom management. Little emphasis on professional qualities was stated. Based on the results, more structured scaffolding and training on reflective practices were proposed. Also, integration of professional qualities into instruction of formal education courses was suggested to promote professional qualities of teachers. Keywords: preservice teachers, blogs, reflection, teacher identity construction, possible-selves theory

ÖZ: Bu çalışma Öğretmenlik Uygulaması dersindeki öğretmen adaylarının zaman azlığı yüzünden sahip olamadıkları birbirleriyle daha fazla iletişim kurma ortamlarını artırmak amacıyla derse eklenen ağ günlüğü (blog) aracını kullanımlarının, onların yansıtıcı düşüncelerine ve öğretmen kimliğini oluşturmalarına olan katkısını incelemiştir. Çalışma iki fazlı bir eylem araştırması şeklinde 2011-2012 ve 2012- 2013 akademik yıllarının güz dönemlerinde, Doğu Akdeniz Üniversitesi’ndeki Yabancı Diller Eğitimi Bölümü, İngilizce Öğretmenliği Programında lisans eğitimi alan 15 öğretmen adayıyla gerçekleştirilmişitr. Öğretmen adaylarıyla yapılan görüşmeler, yansıtıcı ağ günlüğü yazıları ve yorumları bu çalışmanın veri toplama yöntemlerini oluşturmaktadır. Tüm ağ günlüğü içerikleri ve röportajlar nitel açıdan incelenmek üzere word belgelerine aktarılarak kaydedilmiştir. Katılımcıların ağ günlüğü katılımlarını keşfetmek amacıyla frekans analizi uygulanmıştır. Bulgular çalışmanın ilk fazında tüm katılımcıların ağ günlüklerini kullandıkları yönündeyken, ikinci fazda katılımın gönüllülük esasında olmasından dolayı düştüğü yönündedir. Katılımcıların ağ günlüklerinde birbirleriyle olan iletişimlerinin farklı seviyelerde olduğu saptanmıştr. Katılımcıların ağ günlüğü araçlarına karşı aşinalık ve tutumları, ağ günlüğünde yer alan İngilizce yazılı anlatımın yeterliliğine ilişkin algıları, ve katılımcıların kendi aralarında oluşturdukları grup dinamikleri ağ günlüğündeki iletişimi engelleyen faktörler olarak ortaya çıkmıştır. Katılımcıların yansıtıcı düşünce düzeylerini analiz etmek için, çalışmanın amacına uygun olarak uyarlanan bir kuramsal çerçeve kullanılmıştır. Sonuçlar, katılımcıların çoğunun duygularını ifade ettiklerini ve uygulama dersinde edindikleri deneyimlerini tasvir ettikleri yönünde olmakla birlikte, çoğu öğretmen adayının öğretmenlik deneyimine ilişkin tecrübelerini ilgili teorilere bağlamadıklarını ve geleceğe dönük planları üzerinde durmadıklarını işaret etmektedir. Olası-benlikler kuramından yararlanılarak yapılan nitel analiz sonuçları, öğretmen adaylarının ağ günlüklerindeki paylaşımları, öğretmenlik deneyimleri ve filmlerde izledikleri çeşitli öğretmen karakterleri üzerine gerçekleştirdikleri yansıtıcı düşüncelerin, onların “iyi öğretmen nitelikleri” ile ilgili kavramlarını şekillendirmede etkili olduğu, ‘olmak istedikleri’ ve ‘olmaktan kaçındıkları’ olası benliklerini ortaya çıkarmıştır. Bulgular, öğretmen adaylarının sahip olmak istedikleri ve olmaktan kaçındıkları öğretmen özelliklerini, yoğunluklu olarak kişiler arası ilişkiler, öğretim stratejileri ve sınıf yönetimi alanlarından ifade ettiklerini, fakat mesleki niteliklere fazla vurgu yapmadıklarını göstermiştir. Bu sonuçlara göre, pedagojik etkilerin iyileştirilmesi adına, öğretmen adaylarına daha etkili destekleyici sorular ve yansıtıcı düşünce üzerine verilecek eğitimler ile, programda yer alan derslere ek olarak öğretmen adaylarının mesleki niteliklerinin gelişmesine yardımcı olacak konuların eklenmesi önerilmiştir. Anahtar kelimeler: öğretmen adayları, ağ günlüğü, yansıtma, öğretmen kimliğinin oluşumu, olası benlikler kuramı
Doctor of Philosophy in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2018. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: English Language-Study and Teaching; English Teachers-Teacher Identity; Preservice teachers; blogs; reflection; teacher identity construction; possible-selves theory